Rural energy resources utilization and District development - a case study of Nkoranza District - Hugo-Krieger, Kingsley,H. (2012)
A Thesis submitted to the Board of Post - Graduate Studies, University of Science and Technology, Kumasi, in Partial fulfillment of the requirements for the degree of Master of Science in Development Planning and Management.